2004
DOI: 10.1016/s1521-6918(04)00060-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of the short bowel syndrome after extensive small bowel resection

Abstract: Short bowel syndrome (SBS) is a global malabsorption syndrome that results from extensive intestinal resections. It used to be a typical complication of repetitive bowel resections in patients with Crohn's disease. However, due to improved medical and surgical therapies for these patients it currently occurs more frequently as a consequence of vascular disorders in adults (intestinal infarction) and congenital aberrations in children, respectively. Adequate therapy depends on the degree of (small) bowel losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Recently, we showed that SBS patients present deficien cies in vitamins E, D (3,4) and K (3), regardless of venous infusion. Within this context, efforts are primarily devo ted to intestinal adaptation to oral route nutrition (5). Pa tients with severe malabsorption need home PN (5), but it is not a therapeutic option provided by the Brazilian public health system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that SBS patients present deficien cies in vitamins E, D (3,4) and K (3), regardless of venous infusion. Within this context, efforts are primarily devo ted to intestinal adaptation to oral route nutrition (5). Pa tients with severe malabsorption need home PN (5), but it is not a therapeutic option provided by the Brazilian public health system.…”
Section: Introductionmentioning
confidence: 99%
“…The major problems following SBS are chronic diarrhea, dehydration, electrolyte abnormalities, and malnutrition, as a result of severe maldigestion and malabsorption (Keller et al 2004;Duro et al 2008). As regarding renal complication, it is well documented that hyperoxaluria related to malabsorption leads to urolithiasis, oxalate nephropathy, and ultimately development of ESRF (Chadwick et al 1973;Earnest et al 1974;Barilla et al 1978;Das et al 1979;Mole et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with SBS, oral administration of drugs usually becomes difficult because the severity of intestinal failure and absorption capacity vary widely among individuals. This is a significant issue in patients under immunosuppressive therapy to prevent allograft rejection after organ transplantation (Keller et al 2004;Severijnen et al 2004;Duro et al 2008).…”
mentioning
confidence: 99%
“…Thus, a signifi cant number of patients with small intestinal remnants become progressively independent of parenteral nutrition and require diet rich in energy supply (Allard and Jeejeebhoy 1989), which should be distributed over multiple small meals including proper supplementation of vitamins and trace elements (maintenance phase) (Keller et al 2004). However, steatorrhea and diarrhea remain principal manifestations of SBS.…”
Section: Discussionmentioning
confidence: 99%